Relationship between paramagnetic rim lesions and slowly expanding lesions in multiple sclerosis - Calvi, Alberto; Clarke, Margareta A; Prados, Ferran; Chard, Declan; Ciccarelli, Olga; Alberich, Manel; Pareto, Deborah; Rodríguez Barranco, Marta; Sastre-Garriga, Jaume; Tur, Carmen; Rovira, Alex; Barkhof, Frederik (Multiple sclerosis, 2023)
Magnetic resonance imaging (MRI) markers for chronic active lesions in MS include slowly expanding lesions (SELs) and paramagnetic rim lesions (PRLs). To identify the relationship between SELs and PRLs in MS, and their association with disability. 61 people with MS (pwMS) followed retrospectively with MRI including baseline susceptibility-weighted imaging, and longitudinal T1 and T2-weighted scans. SELs were computed using deformation field maps; PRLs were visually identified. Mixed-effects models assessed differences in Expanded Disability Status Scale (EDSS) score changes between the group defined by the presence of SELs and or PRLs. The median follow-up time was 3.2 years. At baseline, out of 1492 lesions, 616 were classified as SELs, and 80 as PRLs. 92% of patients had ⩾ 1 SEL, 56% had ⩾ 1 PRL, while both were found in 51%. SELs compared to non-SELs were more likely to also be PRLs (7% vs. 4%, = 0.027). PRL counts positively correlated with SEL counts (ρ= 0.28, = 0.03). SEL + PRL + patients had greater increases in EDSS over time (beta = 0.15/year, 95% confidence interval (0.04, 0.27), = 0.009) than SEL+PRL-patients. SELs are more numerous than PRLs in pwMS. Compared with either SELs or PRLs found in isolation, their joint occurrence was associated with greater clinical progression.